SOCIAL ISSUES IN JOHN BOYNE’S THE BOY IN THE STRIPPED PYJAMAS - Ida Ayu Made Istri Utami; Komang Ayu Dita Anggraeni; Ni Komang Arie Suwastini; I Wayan Budiarta (Undiksha Press, 2022)
Literature reflects life and shares insights about human life. Holocaust literature focuses on sharing the dark experience of the German Nazis' occupation of Poland in the Second World War. This study aims to identify the representation of social issues in John Boyne’s The Boy in the Striped Pyjamas (2006), one of the Holocaust novels that focuses on children’s experience of the Holocaust. The study employs the interactive qualitative data analysis from Miles, Huberman, and Saldaña (2014), where the data analysis consists of three simultaneous processes of data condensation, data display, and conclusion drawing. It reveals five major social issues included in the novel: the ethnocentric Nazi’s beliefs about German’s superiority, slavery, child labor, class difference, and marginalization toward women. The results imply that children’s literature can also present social issues that may raise awareness about the cruelty of the Holocaust.